On Some Pragmatic Effects of Event Metonymies. - Herrero-Ruiz, Javier (Metaphor & Symbol)
In the literature, event metonymies have been used to explain how language users produce and interpret utterances in which certain events are understood in terms of their sub-events or the overall/complex events they are a part of. This paper attempts to discuss some pragmatic effects of event metonymies which, to the best of our knowledge, have not been explored to date. The first section deals with how certain expressions based on SUB-EVENT FOR EVENT metonymies can be considered synonymous for others in real communicative terms. We, therefore, show how a sound theory of synonymy could not only benefit from the incorporation of referential metonymies but also from the inclusion of SUB-EVENT FOR EVENT metonymies. The second section focuses on how EVENT FOR SUB-EVENT mappings have proven useful to achieve certain pragmatic relevance and mitigation/euphemistic contextual effects which have never been described in the literature. In order to do so, we analyzed a collection of more than 60 expressions (obtained from a study with two native speakers of English) to observe how they can qualify as event metonymies.